Assessing Website Translation Quality - dyah rayna purwaningsih (Jurnal Lingua Idea, 2015)
Translation products now can be found not only in written or printed versions, but also in forms of website pages and website translation is popular in global industry as localization. The global use of the internet encourages websites all over the world to give an easy access to the website visitors by providing them with the translated versions of the sites. As one of new disciplines, translation now begins to develop as many scholars conduct research on it in various aspects. Along with the development, many undergraduate students are also interested in conducting research on translation focusing mainly on translation techniques and translation quality assessment which covers accuracy, acceptability, and readability. This paper is aimed at cutting open dimensions of website translation quality assessment which is based on dynamic translation model (DTM) namely pragmatic, semantic, stylistic, and semiotic dimensions proposed by Bolanos in Hariyanto (2015). Those dimensions are used as a set of parameters to assess the equivalence of the target text (TT), which is related to the acceptability of the translation for the target readers.